A haemodynamic concept in the management of superficial non-saphenous vein thrombosis. (May 2020) - Solimeno, Giovanni; Valitutti, Pasquale
Objective: Through the analysis of the haemodynamic model in the development of superficial non-saphenous vein thrombosis, the authors propose a therapeutic approach which is based on an ultrasound study of the superficial and perforating venous system of the lower limbs. Methods: The authors propose the development of a haemodynamic model in the evolution of superficial non-saphenous vein thrombosis. They analyse three cases to highlight the importance of venous haemodynamics in the development of this condition and its possible complications, such as the progression of thrombosis in the deep vein system through the perforating veins. Results: The evolution of a thrombosis in the venous network of the lower limbs from the peripheral collateral veins to the deep vein can be haemodynamically explained through this model involving the perforating vein system. Conclusions: In the management and treatment of superficial non-saphenous vein thrombosis, it is essential to perform an accurate ultrasound evaluation of the superficial venous system, the deep venous system and the perforator system, according to venous haemodynamic principles. This study proposes a new model to be used in the ultrasonic management and treatment of superficial non-saphenous vein thrombosis.